Preface to the fourth issue of Indian-Pacific Journal of Accounting and Finance - Popoola, Oluwatoyin Muse Johnson (OMJP Alpha Publishing, 2017)
I welcome you with most significant pleasure and honour to the Volume 1 Issue 4 of Indian-Pacific Journal of Accounting and Finance. In this Issue 4, the emphasis is placed on accounting, taxation, business administration, corporate governance and risk management, accounting regulation and financial reporting, and accounting.In the first paper entitled “Board Characteristics, Corporate Performance and CEO Turnover Decisions: An empirical study of listed Non-financial Companies”, Mr Yahya Uthman Abdullahi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia), Dr. Rokiah Ishak (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) and Dr. Norfaiezah Sawandi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) examine the influence of board characteristics and corporate performance on CEO turnover decisions using a sample of 144 firms from non-financial companies listed on the Nigerian Stock exchange between the periods of 2011 to 2015. The study adopts agency and resource dependency theories to support its objectives and applies a logistic regression statistical technique to analyse the results. The results show that board nominating committee has a significant positive relationship with CEO turnover and board gender diversity has a negative influence on CEO turnover. Also, the study also finds that poor corporate performance leads to CEO turnover. In concurring with the findings, the study suggests to the government to enact legislation on gender quota for more women appointment on the board of the corporation to better the performance of the firm, and as well to enhance the monitoring role of the board.